The Generalized Epsilon Function: An Alternative to the Exponential Function - Jónás, Tamás (Acta Cybernetica, 2022)
It is well known that the exponential function plays an extremely important role in many areas of science. In this study, a generator function-based mapping, called the generalized epsilon function is presented. Next, we demonstrate that the exponential function is an asymptotic generalized epsilon function. Exploiting this result and the fact that this new function is generator function-dependent, it can be utilized as a very flexible alternative to the exponential function in a wide range of applications. We should add that if the generator is a rational function, then the generalized epsilon function is rational as well. In this case, the generalized epsilon function is computationally simple and it may be treated as an easy-to-compute alternative to the exponential function. In this paper, we briefly present two applications of this novel function: an approximation to the exponential probability distribution, and an alternative to the sigmoid function on a bounded domain.